Volcanic Landscapes and Associated Wetlands of Lowland Patagonia (The Latin American Studies Book Series,, 2018)
This book presents the most relevant basaltic plateau exposures in the provinces of Neuquén (northern Patagonia) and Santa Cruz (southern Patagonia), and analyzes their geomorphological and morphometric characteristics. The existence of wetland ecosystems near the volcanic plateaus is quantified, thus providing indexes that describe the quantitative relationships between these landscape features. These indexes also make it possible to estimate the development of these wetlands in non-surveyed areas, opening the door for studying remote, isolated areas by means of remote sensing images. In turn, the book proposes a numerical classification system for this type of landscape that summarizes the main geomorphological and hydrological characteristics.